Interobserver variability in interim PET assessment in Hodgkin lymphoma-reasons and solutions. - Thomas W Georgi; Lars Kurch; Dirk Hasenclever; Victoria S Warbey; Lucy Pike; John Radford; Osama Sabri; Regine Kluge; Sally F Barrington (PLoS ONE, 2023)
Introduction Interim PET (iPET) assessment is important for response adaptation in Hodgkin lymphoma (HL). The current standard for iPET assessment is the Deauville score (DS). The aim of our study was to evaluate the causes of interobserver variability in assigning the DS for iPET in HL patients and to make suggestions for improvement. Methods All evaluable iPET scans from the RAPID study were re-read by two nuclear physicians, blinded to the results and patient outcomes in the RAPID trial. The iPET scans were assessed visually according to the DS and, thereafter, quantified using the qPET method. All discrepancies of more than one DS level were re-evaluated by both readers to find the reason for the discordant result. Results In 249/441 iPET scans (56%) a concordant visual DS result was achieved. A "minor discrepancy" of one DS level occurred in 144 scans (33%) and a "major discrepancy" of more than one DS level in 48 scans (11%). The main causes for major discrepancies were 1) different interpretation of PET-positive lymph nodes-malignant vs. inflammatory; 2) lesions missed by one reader and 3) different assessment of lesions in activated brown fat tissue. In 51% of the minor discrepancy scans with residual lymphoma uptake, additional quantification resulted in a concordant quantitative DS result. Conclusion Discordant visual DS assessment occurred in 44% of all iPET scans. The main reason for major discrepancies was the different interpretation of PET positive lymph nodes as malignant or inflammatory. Disagreements in evaluation of the hottest residual lymphoma lesion can be solved by the use of semi-quantitative assessment.